2006
DOI: 10.1021/ja057957s
|View full text |Cite
|
Sign up to set email alerts
|

A New Role for Old Ligands:  Discerning Chelators for Zinc Metalloproteinases

Abstract: In an effort to identify promising non-hydroxamate inhibitors of matrix metalloproteinases (MMPs) several new zinc-binding groups (ZBGs) based on pyridine-derived or aza-macrocycle chelators have been examined. Fluorescence-based enzyme assays have been used to determine the IC50 values for these ZBGs against MMP-1, MMP-3, and anthrax lethal factor (LF). Many of these ligands were found to be remarkably potent, with IC50 values as much as 185-fold lower than that found for acetohydroxamic acid. These ligands a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 26 publications
(47 reference statements)
3
82
0
Order By: Relevance
“…In particular, the catechol moiety of compound 6 appears to be the key functional region of the molecule as it chelates the Zn 2+ ion while aliphatic the five member ring fits nicely into an adjacent hydrophobic pocket (Figures 2A, C). The catechol functionality has been shown previously to be involved in the inhibition of various other metallo-proteases [18][19][20][21]. Interestingly, the hydroxyls groups are also predicted to be simultaneously involved in hydrogen bond interactions with the carboxylates of Glu 687 and Glu 375, side chains coordinating the metal ion (Figures 2A, C).…”
Section: Resultsmentioning
confidence: 82%
“…In particular, the catechol moiety of compound 6 appears to be the key functional region of the molecule as it chelates the Zn 2+ ion while aliphatic the five member ring fits nicely into an adjacent hydrophobic pocket (Figures 2A, C). The catechol functionality has been shown previously to be involved in the inhibition of various other metallo-proteases [18][19][20][21]. Interestingly, the hydroxyls groups are also predicted to be simultaneously involved in hydrogen bond interactions with the carboxylates of Glu 687 and Glu 375, side chains coordinating the metal ion (Figures 2A, C).…”
Section: Resultsmentioning
confidence: 82%
“…Thus, it was possible to reveal the mode of binding of many ZBGs (Jacobsen & Cohen, 2004). Interesting, Cohen and coworkers applied the [HB(pz Ph,Me ) 3 ]ZnOH-fragment to identify ZBGs for the lethal factor of anthrax (Jacobsen et al, 2006). Vahrenkamp and coworker observed both, a bidentate and a monodentate coordination to a [HB(pz Ph,Me ) 3 ]ZnOH fragment, in case of 2-mercaptophenol .…”
Section: Zinc Biomimetic Systemsmentioning
confidence: 99%
“…[4][5][6][7] Although the activity of MMP-8 is naturally regulated by inhibitory proteins, dysregulation of MMP-8 has been found in a variety of disease states, and thus, development of specific small molecule and peptide-based inhibitors for these MMPs has been an active area of research. [11][12][13][14][15] MMP-8 contains a large binding pocket with a flexible loop which has hindered the development of very tight binding inhibitors. 15 It has recently been demonstrated that a small peptide containing a metal binding sequence, tether-metal abstraction peptide (MAP), grafted to dental adhesive polymer formulations, is a potent, effective inhibitor of MMP-8 activity, but the mechanism of inhibition is not known.…”
Section: Introductionmentioning
confidence: 99%